Photocontrollable mononegaviruses - Tahara, Maino; Takishima, Yuto; Miyamoto, Shohei; Nakatsu, Yuichiro; Someya, Kenji; Sato, Moritoshi; Tani, Kenzaburo; Takeda, Makoto (Proceedings of the National Academy of Sciences - PNAS, 2019)
Mononegaviruses are promising tools as oncolytic vectors and transgene delivery vectors for gene therapy and regenerative medicine. By using the Magnet proteins, which reversibly heterodimerize upon blue light illumination, photocontrollable mononegaviruses (measles and rabies viruses) were generated. The Magnet proteins were inserted into the flexible domain of viral polymerase, and viruses showed strong replication and oncolytic activities only when the viral polymerases were activated by blue light illumination.